The Chinese Reality Show “My Dearest Ladies”: A Reflection on the Relationship Between Mother-in-law, Son, and Daughter-in-law in Modern Chinese Families - Tosanguan, Kamonchanok (Lawarath Social E-Journal, 2022)
This article aims to examine the relationship between mothers-in-law, sons, and daughters-in-law as reflected in the Chinese reality show “My Dearest Ladies”. Other issues such as the mothers-in-law’s characters, the presentation of good values to Chinese society, participant selection, and the show development were also studied. The results found that the thirteen families that appeared in the show in all three seasons, reflected how each family had different types of relationships. In some families, the mothers-in-law were dominant, some were the sons and some were the daughters-in-law. Thus, each family would have a person who played a mediator role in compromising problems between family members. It also found that the family where the son-in-law entered the wife's home living together with the mother-in-law would possibly have less conflict than the family where the daughter-in-law lived with the mother-in-law. Most of the mothers-in-law on the show had the characteristics of “Good mother-in-law”. They had kind-hearted, good-humored, compassionate, accepting of the opinions of the new generation, reasonable, respected others, etc. The program also smoothly presented interesting hidden agendas to promote good cultural values to Chinese people that included health-caring for elderly parents, and the mother-in-law’s encouraging her son to take care of her daughter-in-law. Moreover, the daughters-in-law could be diverse from the traditional Chinese values, for example, the daughters-in-law could be older than the sons, and some of them might be married or had children before, and a man could marry and live with his wife's family. Moreover, the show tended to select culturally diverse participants, yet still stay under the One China policy. Although the development of the show in all three seasons has changed due to the Covid-19 situation, the show could manage to present more diverse issues than in the first season.